1986
DOI: 10.3758/bf03211502
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention within and around the field of focal attention: A zoom lens model

Abstract: The operation of attention in the visual field has often been compared to a spotlight. We propose that a more apt analogy is that of a zoom or variable-power lens. Two experiments focused upon the following questions: (1) Can the spatial extent of the attentional focus be made to vary in response to precues? (2) As the area of the attentional focus increases, is there a decrease in processing efficiency for stimuli within the focus? (3) Is the boundary of the focus sharply demarked from the residual field, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

98
1,267
8
40

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,698 publications
(1,413 citation statements)
references
References 41 publications
98
1,267
8
40
Order By: Relevance
“…The effect depends on two factors: first, the location of the distractors in the visual field, and thus presumably on the amount of attentional resources that may be allocated to them. Distractors at fixation receive more attentional resources and are processed more efficiently (Beck and Lavie, 2005;Eriksen & St James, 1986;Kritikos et al, in press). Consistent with this, performance (reaction time and accuracy) was better for targets presented alone at fixation, than at periphery; moreover, distractors had a greater impact when they were presented at fixation rather than periphery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect depends on two factors: first, the location of the distractors in the visual field, and thus presumably on the amount of attentional resources that may be allocated to them. Distractors at fixation receive more attentional resources and are processed more efficiently (Beck and Lavie, 2005;Eriksen & St James, 1986;Kritikos et al, in press). Consistent with this, performance (reaction time and accuracy) was better for targets presented alone at fixation, than at periphery; moreover, distractors had a greater impact when they were presented at fixation rather than periphery.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility for this is that distractors always appeared in the periphery, where relatively fewer attentional resources are directed (Eriksen & St James, 1986). Indeed, Beck and Lavie (2005) and Kritikos, McNeil and Pavlis (submitted) have shown that distractors presented at fixation caused greater interference (slower response times and reduced accuracy) than distractors presented at periphery.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, under this scenario, attention may not be temporarily unavailable for spatial processing-instead, it is available but not in the right shape. I refer to this as the zoom lens explanation of the results (Eriksen & St. James, 1986), and Experiment 2 tested for this possibility. A second alternative is that the lapse in performance is due to general task switching demands (as participants need to switch from the RSVP detection task to the cued visual search task), rather than to an attentional blink induced by the perceptual processing of an RSVP target.…”
Section: Discussionmentioning
confidence: 99%
“…A. Eriksen & Eriksen, 1974; C. W. Eriksen & St. James, 1986;MacLeod, 1991). Kahneman and Chajczyk's (1983) study has further suggested that the extent of processing of a distractor may even extend to its irrelevant dimension.…”
Section: Selective Attention 4 Evidence That Attention Entails Selectionmentioning
confidence: 99%